The Influence of Online Sales Promotion on Impulsive Buying Behavior Among Gen Z Consumers (American Journal of Economics and Business Innovation, 2025)
This study investigated the influence of online sales promotions on impulsive buying behavior among Gen Z consumers in Naawan, Misamis Oriental, Philippines. Leveraging Hawkins Stern’s Impulse Buying Theory, the research examined how specific promotions, including online coupons, price discounts, buy-one-get-one, and free shipping, influenced purchasing decisions. A descriptive-correlational design was employed, utilizing purposive sampling of 300 gen Z consumers with experience in online shopping applications. Results of the Kruskal-Wallis H test that identified the significant difference of impulsive buying behavior when grouped according on the preferred type of online sales promotion among Z Generation consumers revealed that all four promotional strategies yielded statistically significant results at the 0.001 level. Furthermore, regression analysis revealed that price discounts and free shipping are significantly predictive of the extent of impulsive buying behavior suggesting both are antecedent of repeat purchasing due to its perceived value and convenience. On the other hand, online coupons do not show a significant effect. Meanwhile, buy-one-get-one-free variable was excluded from the regression analysis due to collinearity, meaning that this variable was highly correlated with one or more of the other promotional strategies in the model. These findings indicate that for brands that want to help push a Gen Z consumer to purchase impulsively, they should lead with promotions that simply cut the cost of the purchase or provide a high perceived value in exchange for that purchase.